ҚАРАҚАЛПАҚ ТИЛИНДЕ -ЫМ, -ИМ, -М ТАРТЫМ ҚОСЫМТАЛАРЫНЫҢ СЫПАЙЫЛЫҚ МӘНИ БИЛДИРИЎИ - Матжанова, А.Ж. (ILIM hám JÁMIYET, 2024)
The article talks about how the possessive suffix -ım,-im,-m expresses politeness in the Karakalpak language. The main purpose of the article is to find out that in the Karakalpak language, the affixes -ım, -im, -m express the meanings of politeness, caress, respect, and even praise in addition to their function, sometimes in a functional function.